A comparative study on the role of microcredit on agricultural production improvement among resource-poor rural women - Namayengo, Faith Muyonga Mayanja; van Ophem, Johan A. C.; Antonides, Gerrit (Frontiers in Sustainable Food Systems, 2023)
The objective of the study was to evaluate the extent to which borrowing influenced agricultural production for households of women accessing microcredit in a rural agrarian setting in Uganda. A quasi-experimental cross-sectional study design was used to assess changes in different performance indicators of agricultural enterprises for existing and incoming borrowers of Bangladesh Rural and Advancement Committee (BRAC) microfinance. Propensity score matching was used to ensure the comparability of the groups and to assess differences between existing borrowers and in-coming borrowers, before they received their first loan. Results indicated that the major reason for borrowing was education of children. There was no difference in investment in agricultural production between the study groups. The existing borrowers had lower monetary value of all harvested crops and for maize and beans than the in-coming borrowers. Total number of animals owned, types of animals kept and reported monetary value for goats and local cattle were also less for existing borrowers than for in-coming borrowers. In addition, the loan repayment protocols did not match income from agriculture. They need to be tailored to address the latent period between investment and output.